Equitable Maritime-Based Investment in Kepulauan Riau: Evaluation of Policy and Regional Development Direction - YUSTINA, YENI; Dhamayanti, Yustin (Center for Maritime Policy Governance Studies (CMPGS), 2026)
This study examines the issue of unequal maritime-based investment distribution in Kepulauan Riau, an archipelagic province with strategic economic potential due to its proximity to international shipping routes, cross-border trade networks, port infrastructure, and marine-based resources. Although Kepulauan Riau has recorded significant investment growth, investment realisation remains concentrated in Batam, while outer-island districts such as Natuna, Anambas, and Lingga continue to face limited capital inflows, weak infrastructure, and low integration into regional value chains. This study aims to evaluate the direction of investment policy and its contribution to equitable regional development in Kepulauan Riau. Using a qualitative descriptive approach, the study analyses secondary data from the Kepulauan Riau Province Investment and One-Stop Service Agency for 2021–2025, supported by policy review and regional development analysis. The findings show that Batam consistently dominates provincial investment realisation, while Bintan and Karimun experience fluctuating growth and outer-island districts remain structurally marginal. The results also indicate that investment inequality is influenced by uneven connectivity, limited logistics infrastructure, weak investment promotion, insufficient downstream industries, and fragmented institutional coordination. The study concludes that equitable maritime-based investment requires a shift from a Batam-centred growth model toward a spatially inclusive development strategy through thematic economic zones, regional investment potential mapping, infrastructure acceleration, green investment, strengthened investment coordination, and local community integration into maritime value chains.